(3OjhGf GHf ecGfSs - (3GHf ecGfS , YHO GdQMef Hf YHO GdQRGb Hf EHQGgje, aNQ GdOjf CHh GdaQL,J (B794 (3g` s ((3EHQGgje Hf YKeGf CHj GdaVd s)
(3ChdgG (B:s
(3bGd(B: (3jUa SQMI Ydi TGWF Gdfjd(B: (3jGSQMI GdTGWF GdefSGH chKQg Ydi GdjhGbjJ aj CTcGd MUHGA s
(3BNQgG (B:s
(3hPG dGM dj ZRGd fehQ JLQj Ndah eKd GdSdhb Ch fUjO hfaQM hfYed dj ef GdNdhb s
(3fSNI KGdKIs
(3hGdTYQ jfJgj Edi hQbI (B53 (3hjdjg GdfKQs
(3hQO CjVkG JMJ Qbe (B481(3, (B848(3, (B2180s
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdCOHs